2015
DOI: 10.1063/1.4905582
|View full text |Cite
|
Sign up to set email alerts
|

On the motion of unsteady translating bubbles in an unbounded Hele-Shaw cell

Abstract: Unsteady propagating bubbles in an unbounded Hele-Shaw cell are considered numerically in the case of zero surface tension. The instability of elliptical bubbles and their evolution toward a stable circular boundary, with speed twice that of the fluid speed at infinity, is studied numerically and by stability analysis. Numerical simulations of bubbles demonstrate that the important role played by singularities of the Schwarz function of the bubble boundary in determining the evolution of the bubble. When the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…We have applied techniques in exponential asymptotics to describe these solution branches in the limit B → 0. In particular, our analysis leads to the solvability condition (32), which is a relationship that provides an estimate for U in terms of B and m. By comparing with numerical solutions, we have demonstrated that this estimate works very well for small to moderate values of surface tension. The techniques in exponential asymptotics that we employ were developed by Chapman, King & Adams [11] and subsequently used in a variety of problems in applied mathematics.…”
Section: Discussionmentioning
confidence: 82%
“…We have applied techniques in exponential asymptotics to describe these solution branches in the limit B → 0. In particular, our analysis leads to the solvability condition (32), which is a relationship that provides an estimate for U in terms of B and m. By comparing with numerical solutions, we have demonstrated that this estimate works very well for small to moderate values of surface tension. The techniques in exponential asymptotics that we employ were developed by Chapman, King & Adams [11] and subsequently used in a variety of problems in applied mathematics.…”
Section: Discussionmentioning
confidence: 82%
“…It was generally accepted that surface tension was necessary for selecting the pattern [6,26,50,52]. However, recent studies [30,39,60] have demonstrated, by using time-dependent exact solutions without surface tension, that the steady solution with U = 2 is the only attractor for the non-singular unsteady solutions, thus showing that velocity selection in a Hele-Shaw cell is inherently determined by the zero surface tension dynamics. It has been conjectured [60] that a similar scenario holds in domains of arbitrary connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of surface tension selects both a main, symmetric branch of linearly stable steady solutions that persists for all fluxes, along with a countably infinite sequence of unstable 'exotic' bubble shapes; these exist in channels bounded by parallel side walls [19] as well as in unbounded channels [21,22]. Numerical simulations of the time-dependent problem have also been reported [23,24]. Figure 2a shows the bubble shape and speed for the first three solution branches in channels with a rectangular cross section.…”
Section: Introductionmentioning
confidence: 99%